Pengaruh Brand Image Dan Price Terhadap Purchase Intention Pelanggan Nadifa Mart Dengan Trust Sebagai Variabel Mediasi - Sintia Oktadelfia; Mike Yolanda (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The aim of this research is to analyze (1) the influence of brand image on Nadfa Mart customer trust. (2) The influence of price on Nadfa Mart customer trust. (3) the influence of brand image on the purchase intention of Nadfa Mart customers. (4) the influence of price on the purchase intention of Nadfa Mart customers. (5) the influence of trust on the purchase intention of Nadifa Mart customers. (6) The influence of brand image on the trust of Nadfa Mart customers.( 6) the influence of brand image on purchase intention of Nadfa Mart customers with trust as a mediating variable. (7) the influence of price on purchase intention of Nadfa Mart customers with trust as a mediating variable. This type of research is quantitative descriptive research. Using purposive sampling, 120 respondents became the research sample. SEM analysis was carried out using the Smart PLS 4 tool. The results of this research are (1) there is a significant influence between brand image on Nadfa Mart customer trust. (2) There is a significant influence between price on Nadfa Mart customer trust. (3) there is a significant influence between brand image on the purchase intention of Nadfa Mart customers. (4) There is a significant influence between price on the purchase intention of Nadfa Mart customers. (5) There is a significant influence between trust on the purchase intention of Nadfa Mart customers. (6) There is significant influence between brand image on purchase intention of Nadfa Mart customers with trust as a mediating variable. (7) there is a significant influence between price on the purchase intention of Nadifa Mart customers and trust as a mediating variable.